Prospects for micro-insurance in promoting micro-credit in sub-Sahara Africa. (10th November 2014) - Olaosebikan, Olajumoke; Adams, Mike
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study was to, using a case study research design informed by organizational economics theory, to examine the prospects for micro-insurance in promoting micro-credit in a low-income Anglophone country in sub-Saharan Africa – The Gambia. Two main research questions are addressed: first, what is the most appropriate micro-finance institution (MFI) organizational structure to maximize the economic benefits of micro-insurance? Second, what are the financial management and wider economic benefits of the use of micro-insurance by MFIs? Design/methodology/approach – To address our two research questions, we used a semi-structured interview protocol, informed by the organizational economics literature, to interpret the data collected from our field cases. We believe that these intrinsic qualities of case study methodology are particularly apt in the present study, given the complex and emergent nature of micro-finance and micro-insurance in low-income countries such The Gambia. By focusing on case studies in a single country, we also to some extent help control for variations in business environment that could confound interpretations of field data obtained from different jurisdictions. Findings – The results of our study suggest that the mutual (cooperative) structure of credit unions is likely to be the most cost-efficient and effective organizational form for reducing information asymmetries, agency problems and transaction costs. We also observe that micro-insurance can help reduce the risk of loan defaults, thereby increasing returns on savings and lowering the costs of debt. As such, micro-insurance stimulates the demand–supply of financial intermediation in less developed countries and so helps promote economic development. In addition to contributing new insights, our findings have potentially important commercial and public policy implications. Research limitations/implications – We acknowledge that our research is subject to inherent limitations such as the focus on three interviews in three different types of MFI organization while excluding other structural forms of organization such as government-owned/sponsored organizations. Nonetheless, the organizational characteristics of the cases examined in the present study are representative of most MFIs in developing countries. Given the prevalent hierarchical nature of corporate systems in sub-Saharan Africa, the views of the interviewees are also deemed to reflect those of other board members. Nonetheless, we acknowledge that the conclusions from our research may need to be tempered in line with these inherent limitations with the research approach adopted. Practical implications – The insights obtained from our Gambia-based research could be generalized to developing countries elsewhere in sub-Saharan Africa, and indeed, other parts of the developing world. Consequently, the study could be of interest and relevance to international financiers (e.g. the World Bank), aid agencies, governments and other development organizations. Originality/value – Despite its evident business and development potential, academic management research on micro-insurance, and in particular, its role in supporting micro-finance initiatives, is still very much at an embryonic stage. Our study thus seeks to fill this knowledge gap.